Integration of digital cadastral database spatial coordinates towards mapping in Google Earth / Muhammad Fadhil Jasmee, Mohamed Nasri Hj Rani and Jasmee Jaafar - Jasmee, Muhammad Fadhil; Rani, Mohamed Nasri; Jaafar, Jasmee (Universiti Teknologi MARA, Perlis, 2017)
With the advancement of Information and Communications Technology (ICT), locating land parcel physically on the ground is time consuming and costly. In order to facilitate locating land parcel on the ground easily, a base map is required as a guide in determining the land parcel location correlatively on the ground. Google Earth is a free application and provides free satellite images of the earth surface. With the aid of Google Earth satellite images as a base map, locating the land parcel physically on the ground would be easier. This study focuses on the error that may arise when overlaying DCDB spatial coordinates on the Google Earth environment. In this study, the assessments are divided into qualitative and quantitative assessments. The quantitative assessment discussed on the analysis of the coordinate displacement based on the RMSE (Root Mean Square Error) computation, and as for the qualitative assessment, discussion on the shifted DCDB land parcel displayed on the Google Earth platform are discussed. The RMSEx and RMSEy value are computed 1.714 m and 3.883 m respectively. By applying the constant error to the DCDB land parcel, the shift error is eliminated and aesthetical value is achieved and served a diversity of applications.